(untitled) (Journal of the College of Education for Women, 2019)
The variables of quantitative and qualitative Population role in the economic development process and it was said the human center of development and population is the goal of development and its tool , and Iraq suffers from problems in the economic growth and the standard of living and development in general, and if I want him evolution and development sectors must pay for these demographic changes especially , to study and that invest Pmaasb in the interest of the manThe study of the demographic situation in Iraq and at the provincial level to track paths demographic change and its impact on the entry of Iraq to the demographic window due to the change in the age structure of the population and how to use them and invested well in the light of international experiences and the success of Southeast Asian Nations to do so.Where is the population variable quantitatively and qualitatively affect the economic and social changes , political , environmental and demographic variables in the interaction where I am constantly among themselves , and these variables affect the age structure of the population , including most notably birth , which affected fertility population , and because of the development that is going through these changes and their impact on installation age of the population in Iraq, which will lead to the emergence of demographic Dividend , which represents a change of the relationship between the growth of the working age population and population growth dependents, including the demographic variables predictable and turn the strategic development can then predict to enter Iraq and the whole country to this window and Althau economy.Focused research on the study of what deity demographic changes to the population